Is there an ideal method of reconstruction for proximal humerus osteosarcoma? A review of different reconstruction techniques - Ibrahim, Muhammad; Syed Asif Shah; Ahmed, Israr; Khan, Muhammad Arif; Khan, Zeeshan (Journal of the Pakistan Medical Association, 2023)
Osteosarcoma is the commonest primary bone malignancy occurring in patients aged <20, and humerus is the third most common site affected by it. In the past, ablative surgery with poor functional outcomes was the only option, but due to advances in chemotherapy, medical imaging and surgical techniques, patient survivorship and the rate of limb salvage surgery has increased significantly. Over the decades many treatment options have been proposed for the reconstruction of the defect following extirpation of the tumour in the proximal humerus, with every procedure having its merits and demerits. However, there is no agreement on the preferred treatment even in similar age groups, and the best way to reconstruct the proximal humerus remains debatable because the restoration of the function of the shoulder girdle remains primarily dependant on the extent of muscle-loss during tumour resection, available surgical expertise and financial constraints in different health systems. ---Continue